2019
DOI: 10.1542/peds.2018-2591
|View full text |Cite
|
Sign up to set email alerts
|

Blood Lead Levels Among Resettled Refugee Children in Select US States, 2010–2014

Abstract: BACKGROUND: Elevated blood lead levels (EBLLs; $5 µg/dL) are more prevalent among refugee children resettled in the United States than the general US population and contribute to permanent health and neurodevelopmental problems. The Centers for Disease Control and Prevention recommends screening of refugee children aged 6 months to 16 years on arrival in the United States and retesting those aged 6 months to 6 years between 3-and 6-months postarrival. METHODS: We analyzed EBLL prevalence among refugee children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 16 publications
0
22
1
Order By: Relevance
“…In contrast, the BLC of children in Latin America and Caribbean countries between 2000 and 2014 ranged from 25 to 43.2 μg/dL [ 18 ], which was much higher than our study. Another study evaluated 28,427 refugee children in the U.S. between 2010 and 2014 (The top 5 overseas examination countries by arrivals were Thailand, Nepal, Malaysia, Iraq, Kenya) and reported an elevated BLC (> 5 μg/dL) in 19.3% of cases, which was higher than our study [ 16 ].…”
Section: Discussioncontrasting
confidence: 73%
“…In contrast, the BLC of children in Latin America and Caribbean countries between 2000 and 2014 ranged from 25 to 43.2 μg/dL [ 18 ], which was much higher than our study. Another study evaluated 28,427 refugee children in the U.S. between 2010 and 2014 (The top 5 overseas examination countries by arrivals were Thailand, Nepal, Malaysia, Iraq, Kenya) and reported an elevated BLC (> 5 μg/dL) in 19.3% of cases, which was higher than our study [ 16 ].…”
Section: Discussioncontrasting
confidence: 73%
“…There have been few reports of lead exposure in Afghan children, and these identified the use of lead-containing eye cosmetics, a common cultural practice among even very young children and babies from Afghanistan and several Middle Eastern and African countries [48], as the source of lead exposure [49,50]. Studies among resettled Iraqi refugee children show that about 20% of children (versus 13% in our analysis) have blood lead levels over 5 mcg/dL [9,49], while about 1% to 3% of children have levels above 10 mcg/dL [8,10,51]. While potential lead exposures among SIV children were not evaluated in our analysis, US clinicians should ensure that all SIV children 16 years of age and under are evaluated at the domestic medical examination and managed for lead poisoning and malnutrition (including an evaluation for iron deficiency) after arrival [17].…”
Section: Plos Medicinementioning
confidence: 88%
“…However, children aged 1-2 still had lower screening coverage compared with older children. Prior investigations have found a high prevalence of elevated blood lead levels among refugees [12,[31][32][33], and infants and young children are at greatest risk of both lead exposures and the resulting negative health outcomes [33]. Understanding and addressing barriers to lead screening among infants and young children is critical to ensuring appropriate care.…”
Section: Plos Medicinementioning
confidence: 99%
“…In a review of the literature, we found that most analyses based on domestic medical examination data occur at the clinic, state, or local levels [10] and may not represent all recipients of refugee health program services, given the heterogeneity of these populations. Where domestic examination data are pooled across states or sites, analyses are generally limited to a particular condition (e.g., hepatitis B, lead) or population (e.g., children) [11][12][13][14]. Finally, we identified few analyses that reported the proportion of persons screened by condition during the domestic medical examination [10][11][12], which, to our knowledge, prevents assessment of the impact of the domestic examination on screening coverage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation